2011
DOI: 10.1177/1362480611410903
|View full text |Cite
|
Sign up to set email alerts
|

The new political economy of private security

Abstract: This article maps out a new research agenda for interpreting the trajectory and dynamics of domestic private security provision in advanced democratic countries: the 'new political economy of private security'. It proceeds on the basis that the key challenge in this field is to construct an agenda which takes account of how both the economic context (shifts in supply and demand) and the political context (statecentric conceptions of legitimacy) of domestic security simultaneously serve to shape the conduct of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 49 publications
(64 reference statements)
3
60
0
5
Order By: Relevance
“…Lim and Nalla (2014) reported that the number of private security officers in Singapore was three times the number of government police officers. White (2011) noted that "in advanced democratic countries across the world, monopolistic and state-centered systems of security provision are increasingly giving way to more pluralistic systems in which public police forces and private security companies work alongside one another" (p. 85). It is estimated that for every person employed by government, two people are employed in private security organizations (Human Rights and Business Dilemmas Forum, 2011).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Lim and Nalla (2014) reported that the number of private security officers in Singapore was three times the number of government police officers. White (2011) noted that "in advanced democratic countries across the world, monopolistic and state-centered systems of security provision are increasingly giving way to more pluralistic systems in which public police forces and private security companies work alongside one another" (p. 85). It is estimated that for every person employed by government, two people are employed in private security organizations (Human Rights and Business Dilemmas Forum, 2011).…”
mentioning
confidence: 98%
“…The expansion of private security organizations has attracted research by scholars (White, 2011). One area focused upon by scholars is the perceptions and attitudes of personnel.…”
mentioning
confidence: 99%
“…However, since the passage of the PSIA 2001, and the increasingly high profi le role of private security in the post-fi nancial crisis context, there has been a modest rise in this mode of analysis. In particular, White (2010White ( , 2012 , Thumala et al (2011) and Smith and White (2013) have sought to understand how regulation has become not only a mechanism for orientating private security in line with the public good (as surface appearances might suggest), but also a way of reshaping popular perceptions of legitimacy. In a sector where the average UK citizen has a strong expectation that security ought to be delivered by the state, they explore how regulation has become a means by which both state and market actors have attempted to reconstruct private security services in a more ' state-like ' fashion so as to enhance the appeal of these services to often sceptical citizen-consumers.…”
Section: Analysing Security Regulationmentioning
confidence: 99%
“…It focuses on this aspect of security regulation for two reasons. First, while the dynamics of public protection and regulatory capture are extensively documented in the extant literature (see Dal Bo, 2006, for a detailed review), there is very little research on the relationship between public protection and normative legitimation (see White, 2010White, , 2012. This focus thus serves to address a notable gap in this field of research.…”
Section: Introductionmentioning
confidence: 97%